Plato and the contemporary informed consent (2007)
Informed consent is an ethical concept inherent to contemporary medical practice and research. In recognition of its importance, some Plato's ideas are examined, on the basis of the influence upon its definition and reaches, especially what refers to the connection between the quality of a free person and his right to make decisions about his health. © 2007 Corporación Editora Médica del Valle.